Efeito hipolipemiante da Riparina I em modelo de dislipidemia induzida por poloxamer 407 em camundongos C57BL/6 - Carvalho, Kalleu Fernando de Alencar (2025)
Dyslipidemia is characterized as a disorder whose prevalence has been progressively increasing in Brazil and worldwide, and is essential from a public health perspective. The disease can be defined by lipid metabolic alterations that affect the bloodstream, characterized by an increase in total cholesterol, triglycerides, low-density lipoprotein (LDL) and a decrease in high-density lipoprotein (HDL). These alterations are associated with cardiovascular risks and atherosclerosis, which can result in serious cardiovascular events. In view of this, new pharmacological treatments have been based on the investigation of substances of natural origin, such as polyphenols found in tyramine, a monoamine, available in plants, studied for their effects on lipid and carbohydrate metabolism. In this context, riparins (RIP), metabolites of tyramine, have bioactive activity and have been studied for their various biological effects, including anti-inflammatory, antioxidant, anxiolytic and antidepressant effects. The aim of this study was to investigate the lipid-lowering effect of Riparin I (RIP I) in the dyslipidemia model induced by poloxamer P407 in C57BL/6 mice. An acute toxicity study of RIP I was performed according to parameters established by OECD 423 to determine the doses used. Dyslipidemia was induced by a single intraperitoneal injection of P-407 at a dose of 400 mg/kg. The groups were treated four times, as follows: a pretreatment (2 h before administration of P-407), doses of RIP I at concentrations of 100, 50 and 25 mg/kg, followed by treatments 24 h, 48 h and 72 h after intraperitoneal administration of P-407. Two hours after the last treatment, the animals were anesthetized and submitted to blood collection for biochemical dosages of cholesterol, triglycerides and liver markers. At the end of the protocols, the liver was removed for measurement of the antioxidant parameters TBARS, GSH and catalase (U/mg of protein). Low toxicity of RIP I was identified in cardiac, hepatic, renal and brain tissues, being classified in category 5 according to the Globally Harmonized Classification OECD. RIP I was not able to reduce cholesterol and triglyceride levels in animals, however, it demonstrated antioxidant potential through the reduction of TBARS levels, as well as the increase in GSH/GSSG. Additionally, RIP I enabled an increase in HDL cholesterol levels compared to the P407 group. A significant increase in non-HDL cholesterol indices, in the HDLc/TC and TG/HDLc ratios was also identified. In the histological analyses of the dyslipidemia protocol, there were no macroscopic and histopathological changes in the liver tissue, with no changes in aminotransferases (AST and ALT). It is concluded that potential action of RIP I on HDLc and significant antioxidant effect in liver tissue were identified in this model; however, RIP I was unable to reduce triglyceride and total cholesterol levels induced by P407. In summary, future experiments studying riparin I in a chronic model of dyslipidemia induced by a high-fat diet are valid, in order to verify its action, without drug induction, through obesity in mice.